2016
DOI: 10.1177/1049731516628647
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Parenting Support Program to Prevent Abuse of Adolescents in South Africa

Abstract: Violence against children increases in adolescence, but there is a research and practice gap in research-supported child abuse prevention for the adolescent years. A pilot program for low-resource settings was developed in collaboration with nongovernmental organizations, government, and academics in South Africa, using research-supported principles. Method: This study used a pre-post design to test initial effects of a 10-session parenting program with 60 participants (30 caregiver-adolescent dyads) in high-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 34 publications
3
48
0
5
Order By: Relevance
“…Two of the studies were based in South Africa, two in Uganda, one in Liberia and one in Thailand. Of the six studies, two described programmes that were designed to address IPV and CM jointly (Ashburn, Kerner, Ojamuge, & Lundgren, 2016;Hatcher, Colvin, Ndlovu, & Dworkin, 2014;Van den Berg et al, 2013); one was designed to address IPV, but reported unintended outcomes for CM (Abramsky et al, 2014(Abramsky et al, , 2016Kyegombe et al, 2015); and three were designed to address CM, but reported unintended outcomes for IPV (Cluver, Lachman et al, 2016;Cluver, Meinck et al, 2016;Sim, Annan, Puffer, Salhi, & Betancourt, 2014). Table 1 presents four studies which used a randomised controlled trial with a nested qualitative component: REAL Fathers in Uganda (Ashburn et al, 2015); SASA!…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two of the studies were based in South Africa, two in Uganda, one in Liberia and one in Thailand. Of the six studies, two described programmes that were designed to address IPV and CM jointly (Ashburn, Kerner, Ojamuge, & Lundgren, 2016;Hatcher, Colvin, Ndlovu, & Dworkin, 2014;Van den Berg et al, 2013); one was designed to address IPV, but reported unintended outcomes for CM (Abramsky et al, 2014(Abramsky et al, , 2016Kyegombe et al, 2015); and three were designed to address CM, but reported unintended outcomes for IPV (Cluver, Lachman et al, 2016;Cluver, Meinck et al, 2016;Sim, Annan, Puffer, Salhi, & Betancourt, 2014). Table 1 presents four studies which used a randomised controlled trial with a nested qualitative component: REAL Fathers in Uganda (Ashburn et al, 2015); SASA!…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 presents one study which used a pre-post non-randomised design. Sinovuyo Caring Families in South Africa is distinct from other parenting programmes described, as it targets older children who have been identified as having behavioural problems or a suspected history of abuse (Cluver, Lachman et al 2016;Cluver, Meinck et al 2016). Designed specifically to address CM, it also reported outcomes for IPV, both measured quantitatively.…”
Section: Randomised Controlled Trialsmentioning
confidence: 99%
See 3 more Smart Citations